Aggressive angiomyxoma of the pelvis and abdominal wall: Dramatic response to chemical ablation therapy - Li, Liu; Chuang, He; He-Nan, Liu; Dong-Yuan, Li; Qing-Hua, Liang; Wei, Li; Liang-Shan, Li; Ting-Yuan, Li; Xue-Quan, Huang (Frontiers in Oncology, 2023)
Objective Aggressive angiomyxoma (AAM) is a rare, locally aggressive soft tissue neoplasm with a marked tendency for local recurrence after surgery. Although hormone therapy, radiation therapy, and vascular embolization can be performed, we investigated the safety and efficacy of a new chemical ablation protocol for AAM. Methods This study included two female AAM patients from 2012 to 2016. The patients’ clinical and imaging data were collected. The amount of anhydrous ethanol and glacial acetic acid used for chemical ablation was documented, and the management of any complications was detailed. Results The maximum dimensions of the residual tumor were 12.6 cm and 14.0 cm. In one case, the lesion was in the pelvis and protruded into the vulva. Eighty milliliters of liquid with a mixture of glacial acetic acid, anhydrous ethanol, and iohexol (10:9:1) was used for chemical ablation therapy via multipoint injections with a single needle. However, a pelvic fistula developed 1 month later. In another case, the lesion was located in the abdominal wall. The ablation procedure was improved by performing chemical ablation therapy with multiple needles for multi-point injections of smaller than 30 ml injections for each procedure. To date, no recurrence or metastasis has been observed in the two cases. Conclusion The preferred treatment for AAM is complete resection. Chemical ablation therapy is a novel adjuvant therapy for AMM. Nonetheless, more research is needed to confirm these findings.